Impact of Mandatory Corporate Social Responsibility on Beneficiary Institutions Satisfaction in Nepal - Wagle, Sudip (BMC Journal of Scientific Research, 2023)
Corporate Social Responsibility (CSR) became mandatory legislation since 2016/17, in Nepal. The aim of this study is to determine the beneficiary institutions satisfaction from the companies CSR activities in Nepal. Descriptive and causal comparative research design was applied. For that, structured questionnaires were used among 400 registered beneficiary institutions. Mean, standard deviation, correlation and regression analysis were performed by using IBM SPSS 25 version software. The results of this study showed a significant positive correlation between corporate CSR initiatives and the satisfaction of beneficiary institutions in Nepal. Out of eight parameters, three variables make a statistically positively significant contribution (p-value